Young Researchers Workshop on River Management - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 28th October – Faculty of Engineering Technology (FTK) organized the 5th International Young Researchers Workshop On River Basin Environment and Management which managed to attract 55 young researchers from Malaysia, Japan, Thailand, Vietnam, Indonesia and Nepal.